Eighth grade bites - Brewer, Heather (New York, N.Y. : Speak, 2008)
For thirteen years, Vlad, aided by his aunt and best friend, has kept secret that he is half-vampire, but when his missing teacher is replaced by a sinister substitute, he learns that there is more to being a vampire, and to his parents' deaths, than he could have guessed.
Where's the boy? -- Halloween -- Hidden attic -- Search continues -- Otis Otis -- Secrets and sanctuary -- Feeding time -- The book -- Snow and ashes -- A meeting of monsters -- Mr. Otis comes to dinner -- Mr. Craig -- Bound by blood -- Elysia -- The end of a dark journey -- The mark of a vampire.
"First published in the U.S.A.: Dutton Children's Books, 2007"--T.p. verso.
Keywords: Vampires -- Fiction; Orphans -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Horror tales